Development of Ornamental Fish Cultivation to Support Fisheries Tourism In The Sari Nadi Group, Marga District, Tabanan, Bali - S.A.M.Putri, Suryani; Rejeki, I G.A.D. Seri; Arya, I Wayan; Pratama, I Gede Agus Surya; Andriani, A.A.S.Putri Risa; Leba, Meriana Kasi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Koi fish (Cyprinus carpio) is an ornamental fish that has a beautiful body shape and color, so it has high economic value. Indicators of beauty in ornamental fish can be seen in the brilliant color, physical shape and completeness, behavior, and health conditions or stamina. These koi fish are often used as aquarium decorations and are art for consumption enthusiasts. The community demands the beauty of Koi fish, so farmers need to maintain the color of ornamental fish by providing feed that contains color pigments. Carotenoids are the main natural components that make color pigments, positively affecting red and orange colors. Carotenoids can come from spirulina, which contains phycocyanin, chlorophyll-a, and carotene. Carotene is composed of xantophyll (37%), carotene (28%), and zeaxanthin (17%). Providing a source of color pigment in fish feed is one of the efforts to get a bright color evenly distributed in fish. Feeding containing 8% spirulina was effective in increasing color pigmentation in the red swordtail (Xiphophorus helleri). The addition of 1.2% spirulina flour to artificial feed significantly increased color intensity and was the highest result in increasing color intensity of Koi fish.